Investigating the mechanisms underlying effects of testosterone on blood pressure in normotensive and hypertensive rats / Loh Su Yi - Loh, Su Yi (2017)
The influences of sex hormones on the blood pressure regulation have been known since decades. These were evidence by men, with higher testosterone level having higher blood pressure and incidence of hypertension as compared to the age-matched women. Besides, women after menopause who have higher testosterone to estrogen ratio possessing greater blood pressure as compared to women before menopause. Based on these observations, I hypothesized that testosterone might play an important role in causing the blood pressure to increase via affecting the sodium and water handling in the kidney and expression of genes that are involved in the blood pressure regulation in the brain. Therefore in this study, expression of proteins that are involved in sodium and water handling in kidney and gene profiling in the cardiovascular center of the brain were investigated under testosterone influence. This study was performed on normotensive and hypertensive rats which were gonadectomized and subsequently were given testosterone treatment. Two groups were employed which were gonadectomized male normotensive rats receiving sub-chronic (seven days) testosterone treatment and gonadectomized male and female normotensive and hypertensive rats receiving chronic (six weeks) testosterone treatment. Sub-chronic testosterone treatment increased the blood pressure and expression levels of epithelial sodium channel (ENaC) in the kidneys while expression levels of aquaporin (AQP) (AQP-1, 2, 3, 4, 6 and 7) were differentially regulated. Plasma aldosterone, sodium and glucose levels were increased but osmolality and urea levels were decreased. In these rats, co-administration of flutamide (androgen receptor antagonist) and finasteride (5α-reductase inhibitor) prevented the testosterone effects. Chronic testosterone treatment resulted in an increase in the blood pressure but ENaC and AQP expressions in the kidney decreased and increased, respectively. Plasma aldosterone, sodium, osmolality and urea levels were decreased. Chronic testosterone treatment also resulted in up-regulations of 1575, 23 iv and 34 genes in the paraventricular nucleus (PVN), nucleus of solitary tract (NTS) and rostral ventrolateral medulla (RVLM), respectively. However, 252, 23 and 23 genes in these respective regions of the brain were down-regulated. Based on the fold changes of the genes relevant to blood pressure regulation, and following mRNA and protein validations, it was found that two genes in the PVN could be involved in mediating testosterone effects namely Ephx2 and Fcrl2. In overall, testosterone was found to increase the blood pressure, however in kidney, the mechanisms involved differ between periods of exposure. Sub-chronic exposure to testosterone could lead to sodium retention via the related increases in plasma aldosterone and kidney ENaC levels while chronic exposure to testosterone could lead to a decrease in sodium retention via the related decreases in plasma aldosterone and kidney ENaC levels. In both cases, testosterone exposure might also lead to water retention via increasing the kidney AQP expression. In view that chronic testosterone treatment affects the regulation of genes in the cardiovascular center of the brain, mainly the novel Ephx2 and Fcrl2 genes, therefore, it could be suggested that the blood pressure increased following chronic exposure to testosterone might be mediated through the mechanisms involving the brain rather than kidneys.